Prognosis Communication in Pediatric Oncology: A Systematic Review - Estera Boeriu; Alexandra Borda; Eunice Miclea; Amalia-Iulia Boeriu; Dan Dumitru Vulcanescu; Iulia Cristina Bagiu; Florin George Horhat; Alexandra Flavia Kovacs; Cecilia Roberta Avram; Mircea Mihai Diaconu; Luiza Florina Vlaicu; Otniel Dorian Sirb; et al. (MDPI AG, 2023)
Background: While communication plays an important role in medicine, it also often represents a challenge when the topic at hand is the prognosis of a high-risk condition. When it comes to pediatric oncology, the challenge becomes even greater for physicians who have to adapt their discourse to both the child and their family. Methods: Following the PRISMA guidelines, an advanced search on PubMed, Scopus and the Cochrane Library was performed, from 1 January 2017 to 31 October 2022. Demographic data for caregivers, pediatric patients and physicians were extracted, as well as diagnosis, prognosis, presence at discussion, emotional states and impact on life, trust, decision roles, communication quality and other outcomes. Results: A total of 21 articles were analyzed. Most studies (17) focused on caregivers, while only seven and five studies were focused on children and physicians, respectively. Most parents reported high trust in their physicians (73.01%), taking the leading role in decision making (48%), moderate distress levels (46.68%), a strong desire for more information (78.64%), receiving high-quality information (56.71%) and communication (52.73%). Most children were not present at discussions (63.98%); however, their desire to know more was expressed in three studies. Moreover, only two studies observed children being involved in decision making. Most physicians had less than 20 years of experience (55.02%) and reported the use of both words and statistics (47.3%) as a communication method. Conclusions: Communication research is focused more on caregivers, yet children may understand more than they seem capable of and want to be included in the conversation. More studies should focus on and quantify the opinions of children and their physicians. In order to improve the quality of communication, healthcare workers should receive professional training.